Building informal leaders: a mixed-methods study of an army leadership development program for command team spouses - Gleiman, Ashley S. (Kansas State University, 2014)
In this study, the researcher explored the effects of a formal education and leadership development program (LDP), Command Team Spouse Development Program–Brigade Level (CTSDP-BDE), given to spouses of senior military service members (command team spouses) in preparation for brigade-level command team roles and environments. This study employed a nonexperimental, embedded, concurrent, mixed-methods approach to answer the overarching research question: “Can formal educational programs influence life effectiveness for adult participants, assuming informal leadership roles?” Findings from quantitative data indicated that the CTSDP-BDE course influences life effectiveness in participant personal and social abilities and beliefs and organizational skills as defined by scales in the Review of Personal Effectiveness and Locus of Control (ROPELOC) instrument for command team spouses who assume informal leadership roles. No change occurred for Active Involvement or participants’ measures of locus of control (internal and external) because of attending the program. Findings from qualitative data supported quantitative findings, and raise and provide deeper insight into the CTSDP-BDE and spousal education within the United States Army (U.S. Army). Additionally, the researcher demonstrated that formal educational programs could positively influence the informal leadership capabilities of adults. In this study, the researcher used research participants from the CTSDP-BDE, who were housed at the U.S. Army’s School for Command Preparation located in Fort Leavenworth, Kansas. Command team spouse participants (n=40) completed both presurveys and postsurveys over the course of a 7-month data collection period. Likewise, the researcher conducted follow-up, qualitative interviews (n=10) to further investigate the effects of the CTSDP-BDE program.
Keywords: Military spouse; Military; Informal leadership; Volunteerism; Spousal education; ROPELOC; Adult Education (0516)